Prevalence and factors of frailty among community-dwelling older adults: a multimorbidity perspective - Shubing Feng; Pengpeng Wang; Hongxia Huang; Zhenhong Lin; Yuanhang Liu (Frontiers in Public Health, 2026)
Background Frailty is a geriatric syndrome that reduces quality of life and increases social burden. Existing frailty research predominantly focuses on hospitalized or nursing home-residing older adults, while surveys targeting community-dwelling older adults with multimorbidity remain scarce. Objective To investigate the prevalence and influencing factors of frailty among community-dwelling older adults with multimorbidity. Methods A cross-sectional survey was conducted from May to November 2025. Convenience sampling was adopted to recruit multimorbid older adults from five communities in Nanning, Guangxi. Data were collected using a self-designed general information questionnaire, Mini Nutritional Assessment Short-Form (MNA-SF), Barthel Index (BI), Pittsburgh Sleep Quality Index (PSQI), and Groningen Frailty Indicator (GFI). Univariate analyses and multivariate binary Logistic regression were performed to identify factors associated with frailty. Results A total of 346 multimorbid community-dwelling older adults were enrolled, including 183 frail individuals (52.9%) and 163 non-frail individuals (47.1%). Multivariate Logistic regression revealed that age, hospital admission due to acute events in the past year, nutritional status, residential area, primary caregiver type, and activities of daily living (ADL) were independent influencing factors of frailty. Compared with participants aged 60–70 years, the risk of frailty was significantly higher in those aged 70–80 years (OR = 2.644, 95%CI: 1.030–6.790) and ≥80 years (OR = 4.923, 95%CI: 1.870–12.960). Older adults admitted for acute events exhibited higher frailty risk than those without acute admission (OR = 1.841, 95%CI: 1.035–0.274). Rural residents had higher frailty risk than urban counterparts (OR = 0.338, 95%CI: 0.191–0.600). Normal nutritional status (OR = 0.227, 95%CI: 0.155–0.496) and full ADL independence (OR = 0.210, 95%CI: 0.056–0.794) were protective against frailty. Taking self-care as the reference group, frailty risk was markedly lower among older adults cared for by spouses (OR = 0.387, 95%CI: 0.158–0.947), children (OR = 0.354, 95%CI: 0.148–0.845), or professional caregivers (OR = 0.241, 95%CI: 0.072–0.811). Conclusion The prevalence of frailty is relatively high among community-dwelling older adults with multimorbidity. Age, nutritional status, residential environment, history of acute-event hospitalization in the past year, primary caregiver type, and ADL capacity are independent risk factors for frailty. Primary community health services should establish integrated screening and intervention systems targeting high-risk groups including advanced-age, malnourished, functionally impaired older adults and those lacking caregiver support.